1996
DOI: 10.1111/j.1365-2818.1996.tb04794.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies of pseudowollastonite for biomedical application

Abstract: Summary Pseudowollastonite ceramic (psW) composed of CaO·SiO2 was found to be bioactive in a simulated body fluid environment. The chemical reaction initiated at the material surface resulted in hydroxyapatite (HA)formation. These bone‐bonding properties are essential for securing the necessary physico‐chemical integration of the material with living bone. Materials behaving in this way can be considered for potential biomedical application as bone tissue substitute for a natural bone repair or replacement as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
63
1
4

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 18 publications
5
63
1
4
Order By: Relevance
“…In addition, Ohura et al (15) showed that a calcium silicate binary glass, called CS and containing 48.3 wt% CaO and 51.7 wt% SiO 2 , it joins firmly to bone tissue. Subsequently, De Aza et al (16)(17)(18)(19) showed, for the first time, that a crystalline compound other than hydroxyapatite and containing no phosphate (viz. wollastonite, CaSiO 3 ) not only exhibits a high bioactivity in both simulated body fluid (SBF) and parotid saliva, but also bonds strongly to bone tissue (20,21).…”
Section: Reactivity In Physiological Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Ohura et al (15) showed that a calcium silicate binary glass, called CS and containing 48.3 wt% CaO and 51.7 wt% SiO 2 , it joins firmly to bone tissue. Subsequently, De Aza et al (16)(17)(18)(19) showed, for the first time, that a crystalline compound other than hydroxyapatite and containing no phosphate (viz. wollastonite, CaSiO 3 ) not only exhibits a high bioactivity in both simulated body fluid (SBF) and parotid saliva, but also bonds strongly to bone tissue (20,21).…”
Section: Reactivity In Physiological Mediamentioning
confidence: 99%
“…Especially after Ohura et al (15) and De Aza et al (16)(17)(18)(19) demonstrated the formation of a CHA layer on Ca-SiO 2 glasses and wollastonite (CaSiO 3 ) respectively, both of which contain no phosphate ions and bond to bone tissue (20, 21. 26 -27).…”
Section: Reactivity In Physiological Mediamentioning
confidence: 99%
“…Kokubo et al [258,259] and Ohtsuki et al [260] showed that the CaO-SiO 2 components contributed mainly to the bioactivity of the CaOÁSiO 2 -based glass and ceramics. De Aza et al [261][262][263][264] pointed out that wollastonite ceramics (CaSiO 3 ) were bioactive and Nonami and Tsutsumi [265] working with diopside (CaO-MgO-2SiO 2 ) ceramics found that an apatite layer was formed on the surface of diopside ceramics implanted into the bone of rabbits and monkeys. However, clinical applications have been sparse on account of their relatively poor mechanical properties.…”
mentioning
confidence: 99%
“…Los detalles de la preparación y caracterización de la pseudowollastonita se pueden encontrar en publicaciones anteriores (9,10).…”
Section: Methodsunclassified
“…En la mayoría de los casos, se observó la formación de una capa intermedia, rica en sílice, seguida por otra capa exterior de fosfato cálcico (1)(2)(3)(4)(5)(6)(7). Estudios previos in vitro e in vivo han puesto de manifiesto que la wollastonita (CaSiO 3 ), material cerámico policritalino bioactivo, forma una capa de hidroxiapatito (HA) en su superficie al entrar en contacto con suero fisiológico artificial (SFA), saliva humana parotidea o al ser implantada, uniéndose a través de dicha capa directamente al tejido óseo (3,4,(8)(9)(10)(11)(12).…”
Section: Introduccionunclassified